2020
DOI: 10.26434/chemrxiv.12698462
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Voltammetric pH Measurements in Unadulterated Foodstuffs, Urine, and Serum with 3D-Printed Graphene/poly(lactic Acid) Electrodes

Abstract: The pH of a system is a critical descriptor of its chemistry – impacting reaction rates, solubility, chemical speciation, and homeostasis. As a result, pH is one of the most commonly measured parameters in food safety, clinical, and environmental laboratories. Glass pH probes are the gold standard for pH measurements, but suffer drawbacks including frequent recalibration, wet storage of the glass membrane, difficulty in miniaturization, and interferences from alkali metals. In this work, we describe a voltamme… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Plots of the peak potential (E p ) and pH (Figure S4D) revealed that the linear relationship can be expressed as follows: E p = −0.0690pH + 0.9099 (R 2 = 0.9988). It is clearly seen that the linear slope, 69.0 mV pH −1 , is close to the theoretical value, 59.2 mV pH −1 , 58 implying that the numbers of protons and electrons transferred in the reaction of OTC were equal.…”
Section: Effect Of Phmentioning
confidence: 99%
“…Plots of the peak potential (E p ) and pH (Figure S4D) revealed that the linear relationship can be expressed as follows: E p = −0.0690pH + 0.9099 (R 2 = 0.9988). It is clearly seen that the linear slope, 69.0 mV pH −1 , is close to the theoretical value, 59.2 mV pH −1 , 58 implying that the numbers of protons and electrons transferred in the reaction of OTC were equal.…”
Section: Effect Of Phmentioning
confidence: 99%
“…45 In addition, the NaOH activation can induce pH-sensitivity in the G/PLA 3D-printed electrode response. 46 Thus, the electrochemical behavior of the electrode in the presence/absence of TBHQ (40 μmol L −1 ) was studied in a buffered solution controlling the pH from 2.0 to 7.0 using BR buffer, by square wave voltammetry (SWV) as shown in Figure 3 (Figure 3A− F). For the G/PLA 3D-printed electrode, the increase in pH results in peak shifting to lower potential with current decrease.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Whilst these are easy to make, it is difficult to make smaller and complex geometry electrodes. Therefore, recently thermoplastics such as poly (meth-methacrylate) [19][20] and poly lactic acid (PLA) [21][22] have been more widely used as binders and studies have shown these can be patterned and molded to make sub-millimeter sized electrodes 20,[23][24][25] . Further developments have been achieved through the utilization of carbon composite thermoplastics in 3D printing, which has provided the scope to fabricate electrodes of complex geometries [26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%